Modeling of blast furnace melt processes when changing the program of charging the burden (Modern Problems of Metallurgy, 2022)
The publication presents the results of a predictive assessment of the modeling of processes and final indicators of blast-furnace smelting with a change in the charge loading program for a blast furnace with a volume of 1719 m3, followed by comparison with the actual results obtained. Modeling was carried out using a mathematical model of blast-furnace smelting, which, in contrast to obtaining balance indicators, makes it possible to obtain knowledge about the mechanism of the processes due to which changes occur, including the uneven distribution of charge materials on the top of the blast furnace. The change in the distribution of the ore load was expressed in a decrease by 15-20% of the ore load in the radial ring zones 1-3, where their values in the first period did not exceed 1.0 and an increase in the ore load in the most loaded radial ring zones 5-10 by 2-10%. This led to the displacement of gas isotherms in the central and intermediate radial annular zones upwards, and only in the peripheral zone downwards. At the same time, the temperature difference between the gas and the charge also increased, especially in the upper part, and the softening and melting zone shifted upwards in most of the radial annular zones, except for the peripheral one - 10. The resulting value of heat transfer in the charge column is the gas temperature at the outlet of the charge column. The nature of its change along the radius of the blast furnace is the same for the values calculated by the model and those measured in the blast furnace and indicates an increase in the temperature of the flue gases when using the program for loading the second period. Similar curves for the degree of use of CO gas, obtained by calculation according to the model. From the obtained results, it follows that in lightly loaded radial annular zones, heating to a given temperature occurs at higher horizons, and in heavily loaded ones, at the lowest-high-temperature horizons, requiring heat transfer intensification and measures to improve energy utilization. Without additional measures, a decrease in the use of heat and a corresponding increase in the temperature of the exhaust gases with a reduction in the degree of use of the reducing ability of gases is inevitable, which is obtained as a result of calculations.